2010
DOI: 10.1016/j.jcsr.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Headed steel stud anchors in composite structures, Part II: Tension and interaction

Abstract: The Newmark Structural Engineering Laboratory (NSEL) of the Department of Civil and Environmental Engineering at the University of Illinois at Urbana-Champaign has a long history of excellence in research and education that has contributed greatly to the state-of-the-art in civil engineering. Completed in 1967 and extended in 1971, the structural testing area of the laboratory has a versatile strong-floor/wall and a three-story clear height that can be used to carry out a wide range of tests of building materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…Accordingly, the shear strength of large diameter and high strength welded Advances in Civil Engineering stud connectors could also be accurately estimated by AASHTO LRFD [19] as the conventional welded stud connectors. Since the failure modes of the push-out tests are the stud shank fracture without the splitting of the concrete blocks, the shear strength of welded stud connectors could be regarded as the tensile strength of the studs, which is also veri ed by Pallarés and Hajjar [4,5] in the research of welded stud connectors with conventional diameters.…”
Section: Evaluation Of Shear Strengthmentioning
confidence: 95%
See 1 more Smart Citation
“…Accordingly, the shear strength of large diameter and high strength welded Advances in Civil Engineering stud connectors could also be accurately estimated by AASHTO LRFD [19] as the conventional welded stud connectors. Since the failure modes of the push-out tests are the stud shank fracture without the splitting of the concrete blocks, the shear strength of welded stud connectors could be regarded as the tensile strength of the studs, which is also veri ed by Pallarés and Hajjar [4,5] in the research of welded stud connectors with conventional diameters.…”
Section: Evaluation Of Shear Strengthmentioning
confidence: 95%
“…Lam [3] performed 72 static push-out tests on welded studs to determine the shear strength of welded stud connectors embedded in hollow-core slabs. Pallarés and Hajjar [4,5] reviewed a large number of push-out and pull-out tests on welded stud connectors and proposed formulas for the limit states of welded stud connectors subjected to shear force, tension force, and combined tension and shear force. Lin et al [6] also investigated the behavior of welded stud connectors subjected to combined tension and shear loads, and an improved shear-tension interaction strength equation was recommended.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, the AISC [23,24] has included the results from the extended research conducted by Pallares and Hajjar [25,26] on headed steel stud anchors as a force transfer mechanism in composite constructions, including composite wall systems. The capacity of a single headed stud can be calculated by the following equation for studs governed by steel shank failure…”
Section: Code Shear Capacity Methods For Headed Studs In Composite Wamentioning
confidence: 99%
“…The most critical scenario is that they are subjected to combined shear and tension as in the case of connections between the tension members and sandwich deck as shown in Figure 2a; connections between the horizontal beams and shear walls as shown in Figure 2c and 2d; high shear region of the beam and slab, and sandwich structures subjected to impact and blast as shown in Figure 2e and 2f. The shear resistance of the headed shear stud connectors in the steel-concrete composite structures has been extensively studied by Viest [9], Driscoll and Slutter [10] [29], Klinger and Mendonca [30], and Pallarés and Hajjar [31]. The resistance of the anchorage under combined shear and tensile load was studied by Pallarés and Hajjar [31], McMakin et al [32], Sari et al [33], and Mirza and Uy [34].…”
Section: Introductionmentioning
confidence: 99%
“…The shear resistance of the headed shear stud connectors in the steel-concrete composite structures has been extensively studied by Viest [9], Driscoll and Slutter [10] [29], Klinger and Mendonca [30], and Pallarés and Hajjar [31]. The resistance of the anchorage under combined shear and tensile load was studied by Pallarés and Hajjar [31], McMakin et al [32], Sari et al [33], and Mirza and Uy [34]. From these literatures, it can be found that most of these experimental and numerical studies were carried out on headed studs to investigate their resistances against tension and shear forces as well as combined shear and tensile forces.…”
Section: Introductionmentioning
confidence: 99%